The Challenges and Paradigm Shift in Promoting Teachers' Professional Development through Public Courses - Wenyan HE (Human-Centric AI and Future Existential Dynamics, 2026)
As a distinctive teaching-research activity in China’s basic education, public courses have played an important role in promoting teachers’ professional development. However, in practice they have gradually acquired tendencies towards formalisation and performance, which undermine their essential function as pedagogical research. By tracing the institutional evolution and functional transformation of public courses, this paper points out the real-world dilemmas they currently face in facilitating teacher reflection, student participation, and the functioning of teaching-research communities. The study analyses the underlying causes from four aspects: evaluation mechanisms, teacher psychology, professional support, and school culture. On this basis, it proposes a paradigm-shift path oriented towards evidence-based practice. This path advocates a problem-oriented, evidence-based, and collaborative inquiry model of teaching research, and, through conceptual renewal, process restructuring, and ecological empowerment, aims to transform public courses from instructional showcases into in-depth research activities, making them a truly effective platform for teachers’ professional development.